Correlation analysis between OCT evaluation and postoperative visual prognosis of patients with age-related macular degeneration complicated with cataract - Lei Zhang; Yuanxiang Luo (BMC Ophthalmology)
Abstract Objective To explore the correlation between optical coherence tomography (OCT) evaluations and postoperative visual prognosis in individuals with AMD complicated with cataract, and to investigate the clinical applications of these evaluations for predicting visual outcomes. Methods We retrospectively analyzed the clinical data of 132 individuals (132 eyes) with AMD complicated by cataract, admitted to our hospital from April 2022 to January 2024. All patients underwent surgical treatment and were categorized into two groups based on their visual prognosis after 6 months: the “good prognosis (GP)” group (best corrected visual acuity decrease < 0.1 logMAR) and the “poor prognosis (PP)” group (best corrected visual acuity decrease ≥ 0.1 logMAR). We evaluated OCT parameters including central retinal thickness (CRT), central macular thickness (CMT), subfoveal choroidal thickness (SFCT), and total average macular thickness (TR). Pearson correlation analysis was employed to assess the relationship between these OCT parameters and postoperative visual outcomes. Additionally, receiver operating characteristic (ROC) were used to calculate the predictive value of OCT measurements for identifying poor postoperative visual prognosis in this patient cohort. Results Preoperative OCT results showed significantly higher values for CMT, CRT, TR, and SFCT in the PP group compared to the GP group (P < 0.05). Pearson correlation analysis revealed a positive association between postoperative visual acuity and these OCT parameters. Logistic regression modeling identified CMT, CRT, TR, and SFCT as key predictors of poor visual prognosis in AMD patients with cataract. ROC analysis showed that combining these parameters improved the prediction accuracy, with an area under the curve (AUC) of 0.993, sensitivity of 99.87%, and specificity of 95.30%, which were significantly higher compared to single-index evaluations (P < 0.05). Conclusion CMT, CRT, TR, SFCT are obviously related to the postoperative visual prognosis in patients with AMD complicated by cataract. The combined evaluation of these OCT parameters demonstrates high predictive efficiency for poor postoperative visual prognosis and can serve as an important assessment index for evaluating the postoperative visual prognosis in this patient population.